Habitat Use Patterns and Identification of Essential Habitat for an Endangered Coastal Shark With Vertebrae Microchemistry: The Case Study of Carcharhinus porosus - Feitosa, Leonardo Manir; Dressler, Valderi; Lessa, Rosangela Paula (Frontiers in Marine Science, 2020)
Sharks are among the most endangered and data poor vertebrates in the world. The lack of information regarding their habitat use is especially concerning since these are crucial for the establishment of priority areas for species conservation. Investigating the trace elements present in shark vertebrae has become an interesting tool to analyze species habitat use over individuals’ lifetimes. Therefore, we applied vertebrae microchemistry to investigate habitat use of Carcharhinus porosus in Brazil’s Northern Coast (BNC). We also discuss methodological issues that must be addressed in the future to make microchemistry studies with elasmobranchs at low latitudes more robust. Vertebrae from seventeen individuals sampled in the 1980s (n=8), and in 2017 and 2018 (n=9) were evaluated through laser ablation inductively coupled plasma mass spectrometry. We analyzed five elements known to reflect environmental characteristics (Ba, Ca, Mg, Mn, and Sr) by sex, seasons, decades of capture, and life stages. Since Ca is the most abundant element in the vertebrae, we calculated element:Ca ratios and employed these proportions for all statistical analysis. We also used fisheries-independent catch data from the 1980s to test if the BNC is a nursery area for C. porosus. We found significant differences in element concentrations between sexes in both multi and single-element analysis, while decades differed only in the multi-element and Sr:Ca. Furthermore, seasons differed in both multi-element and Mg:Ca and Ba:Ca ratios. We did not find differences between life stages. Neonate multi-element signatures yielded three major groups, thus suggesting that the species has at least three birthing grounds in the area. Despite the occurrence of individuals of all sizes, adults show a more distinct occurrence pattern. Our results point towards the hypothesis that the BNC is an essential habitat for this species since its whole life cycle occurs in this area. Therefore, the BNC is a critical area for its conservation. We reinforce that future studies with strictly tropical species should investigate the effects of metabolism, the species’ growth rate, and the validation of other elements capable of demonstrating fine-scale changes in habitat to reduce the inherent noise in microchemistry studies.